Nutritional and antioxidant potential of rice flour enriched with kersting’s groundnut (Kerstingiella geocarpa) and lemon pomace - Olugbenga O. Awolu; Magoh A. Osigwe (International Journal of Food Studies)
This study was designed to enhance the nutritional quality, antioxidant properties and product utilization potentials of locally produced ‘Igbemo’ rice flour by adding Kersting’s groundnut and lemon pomace. Kersting’s groundnut is an underutilized legume while lemon pomace is a byproduct of lemon utilization; both meant to enhance the protein quality, antioxidant potential and fibre contents of the composite flour. The dependent variables were minerals composition, amino acid profile, antioxidants and antinutrients properties, in-vitro protein digestibility and in-vitro carbohydrate digestibility. The result showed that blends with higher lemon pomace of 10.00 g had the best calcium, iron, potassium and magnesium contents and antioxidant contents, while blends with highest Kersting’s groundnut (20.00 g) had the best zinc content. The anti-nutrients in the blends were generally low and safe for consumption.